High Throughput Sequencing and Network Analysis Disentangle the Microbial Communities of Ticks and Hosts Within and Between Ecosystems - Estrada-Peña, Agustín; Cabezas-Cruz, Alejandro; Pollet, Thomas; Vayssier-Taussat, Muriel; Cosson, Jean-François (Frontiers in Cellular and Infection Microbiology, 2018)
We aimed to develop a framework, based on graph theory, to capture the ecological meaning behind pure pair comparisons of microbiome-derived data. As a proof of concept, we applied the framework to analyze the co-occurrence of bacteria in either Ixodes ricinus ticks or the spleen of one of their main hosts, the vole Myodes glareolus. As a secondary lymphoid organ, the spleen acts as a filter of blood and represents well the exposure to microorganisms circulating in the blood; including those acquired and transmitted by ticks during feeding. The microbiome of 301 and 269 individual tick and vole samples, respectively, were analyzed using next generation sequencing (NGS) of 16S rRNA. To assess the effect of habitat on ecological communities of bacteria associated to ticks and voles, two different biotopes were included in the study, forest and ecotone. An innovative approach of NGS data analysis combining network analysis and phylogenies of co-occuring of bacteria was used to study associations between bacteria in individual samples. Of the 126 bacterial genera found in ticks and voles, 62% were shared by both species. Communities of co-occurring bacteria were always more phylogenetically diverse in ticks than in voles. Interestingly, ∼80% of bacterial phylogenetic diversity was found in ∼20% of ticks. This pattern was not observed in vole-associated bacteria. Results revealed that the microbiome of I. ricinus is only slightly related to that of M. glareolus and that the biotope plays the most important role in shaping the bacterial communities of either ticks or voles. The analysis of the phylogenetic signal of the network indexes across the 16S rRNA-derived tree of bacteria suggests that the microbiome of both ticks and voles has high phylogenetic diversity and that closest bacterial genera do not co-occur. This study shows that network analysis is a promising tool to unravel complex microbial communities associated to arthropod vectors and vertebrate hosts.